PENGARUH KREATIVITAS DAN INOVASI TERHADAP KEUNGGULAN BERSAING (Survey Pada Industri Kreatif di Kota Bandung) - Titi Laras (Indonesian Journal of Economics and Business, 2012)
The better condition of Indonesia Economy and the real condition post economic crisis, the better is the growth of industrial sector. Creative industry comes from the utilization of individual creativity, skill, and talent to create welfare and job fields through the creation and the implementation of individual creativity and creation. Creative industry can stimulate youth innovation and creativity and has positive social impact. The aim of this study is to gain the picture of creativity, innovation, competitive advantage and company performance in the creative industry in Bandung. It is also to seek and find the empiric proof of the research so that it can get the answers of the influence of creativity and innovation to competitive advantage partially or simultaneously.This research used the method of causal descriptive-survey, which states that there is a reciprocal relationship between the free variables, which are company creativity and innovation, and the bound variables, which are competitive advantage. Population in this company is all 5291 creative industries in Bandung, which cover 15 business sectors, and the sample is 182 creative industry companies in Bandung, which cover 15 business sectors. The technique of sampling used is Proportional Stratified Random Sampling. The tool of analysis is Structural Equation Modeling (SEM)-PLS-PM. There are second orders, with the first one is the dimension and the second one is the indicator through the use of XLSTAT software 2011 version.The result of the research shows that average companies’ creativity has high creativity force, companies’ innovation has been well implemented, competitive advantage has high competitive force, and average company performance in creative industries in Bandung have high performance. However, based on the result of hypothesis test it is found that there are positive and significant influences to company creativity and innovations toward competitive advantage partially and simultaneously.